Ligand Engineering for Improved All‐Inorganic Perovskite Quantum Dot‐MoS2 Monolayer Mixed Dimensional van der Waals Phototransistor. Issue 7 (10th April 2019) - Wu, Hualin; Kang, Zhuo; Zhang, Zihan; Si, Haonan; Zhang, Suicai; Zhang, Zheng; Liao, Qingliang; Zhang, Yue
Abstract: Combining intriguing physical properties of 2D crystals and intrinsically remarkable optical properties of halide perovskite quantum dots (QDs), the 0D–2D perovskite QD–based mixed dimensional van der Waals heterostructure (MvdWH) is considered as promising for optoelectronic applications. Even though the interfacial electronic structure of MvdWHs is sufficiently engineered to manipulate the charge carrier behavior, the issue of interfacial charge transfer efficiency originating from the residue ligands that are inevitably introduced by the QDs is still prominently remained. From this perspective, for the first time, a solution‐processed surface ligand density control strategy is demonstrated to balance the QD surface passivation and the interfacial charge carrier extraction and injection efficiency in the 0D–2D MvdWH system. The accurate adjustment of ligand density outside QDs enables the subsequent modulation on interfacial charge carrier transfer efficiency from the aspect of electronic and optoelectronic properties. Furthermore, such kind of ligand engineering toward MvdWH interface is substantially demonstrated in a photogating mechanism–based phototransistor with an improved photoresponsivity as high as 1.13 × 10 5 A W −1 . These results may push forward the evolution of 0D–2D mixed dimensional van der Waals optoelectronics. Abstract : A ligand engineering strategy to balance the surface passivation of perovskite quantum dots and interfacial charge carrier transfer efficiency is demonstrated in a mixed‐dimensional van der Waals heterostructure system, of which sufficient optical characterizations and corresponding phototransistors' optoelectronic performance with an order of magnitude improved photoresponsivity of 1.13 × 10 5 A W −1 is verified as well.